Dialog Antar Agama sebagai Implementasi Pendidikan Perdamaian - Nur Ashilla, Fathya; Tari, Natia; Rizki Akbar, Muhammad (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2024)
Interfaith dialog plays an important role in promoting peace and understanding in diverse societies. This study examines the implementation of interfaith dialog as a key component of peace education. Using a comprehensive literature review approach, this study explores the role of interfaith dialog in the implementation of peace education. The Halaqah Damai program emerged as a concrete step to nurture tolerance, break down stigma, and foster a harmonious and inclusive society. By encouraging and utilizing dialogue as a connecting tool among individuals of different religions, peace education initiatives aim to foster mutual understanding and cooperation among Indonesia's diverse population.